Espacio público en conjuntos habitacionales - Guzmán González, Leticia (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The urban development zones in the city of Morelia increasingly tend to expand; In the urban landscape, the development of residential condominiums is observed, which has caused real estate companies to capitalize on “security” and “aesthetics” as one of the elements of sales and greater capital gains; although in many cases the relationship with the city is fragmented since individuals, faced with the need to feel in a safe place, isolate themselves from society at considerable distances and are separated from supply and recreation facilities, which leads to a high cost of living in these developments, because the neighbors assume the cost of maintaining green areas and surveillance, which strictly corresponds to the City Council. In this research it is assumed that the non-use or abandonment of common areas denotes the lack of appropriation and identity of the inhabitants. Among other words, it is assumed that a sense of community is not achieved. Once the developments are inhabited and the construction company abandons the site, a marked process of deterioration and abandonment of the green public areas is observed. This is seen as evidence of the contrast between the construction company’s project and the social reality of the development’s inhabitants.

Las zonas de desarrollo urbano en la ciudad de Morelia cada vez tiende a expandirse; en el paisaje urbano se observa el desarrollo de condominios habitacionales, lo que ha originado que las empresas inmobiliarias hayan capitalizado la “seguridad” y “estética” como uno de los elementos de venta y mayor plusvalía; aunque en muchos de los casos se fragmenta la relación con la ciudad ya que los individuos ante la necesidad de sentirse en un lugar seguro se autoaislan de la sociedad a distancias considerables y están apartados de equipamientos de abastos y recreación, lo que con lleva a un alto costo el vivir en estos desarrollos, porque los vecinos asumen el costo de mantenimiento de áreas verdes y vigilancia, que en sentido estricto corresponde al Ayuntamiento. En la presente investigación se asume que el no uso o abandono de las áreas comunes denota la falta de apropiación e identidad de los habitantes. Entre otras palabras, se asume que no se logra el sentido de comunidad. Una vez que los desarrollos son habitados y la compañía constructora abandona el sitio, se observa un marcado proceso de deterioro y abandono de las áreas públicas verdes. Esto asume como una evidencia del contraste entre el proyecto de la compañía constructora y la realidad social de los habitantes del desarrollo.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2023-1521; Abandono; Estética; Comunidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16762